EFFECT OF ALPHA LIPOIC ACID IN TREATMENT OF TYPE 2 DIABETES - Panda, Priyambada; Panda, Sitansu Kumar; Mishra, Tapaswini (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: Antioxidant probably can prevent the progression and complications of Type 2 diabetes mellitus (T2DM). Due to effectiveness of alpha lipoic acid (ALA) as an antioxidant, this study was done in T2DM patients to evaluate the effect of ALA on their diabetic status, lipid profile, and oxidative stress (OS) status. Methods: A total of 35 patients with diabetes were selected randomly who were under insulin treatment mainly and grouped as Group A.â€ Another age- and sex-matched healthy controls selected grouped as B.â€ Both groups supplemented with ALA (300 mg/day) for 6 months continuously. All parameters were tested before and after the supplementation. Results: There was a significant decrease in fasting blood sugar from 161 to 122 mg/dl in Group Aâ€ and from 98 to 90 mg/dl in Group B.â€ Postprandial blood sugar (PPBS) and glycosylated hemoglobin (HbA1c) levels also significantly decreased from 211 to 158 mg/dl and 8.81% to 7.2%, respectively, in Group A.â€ PPBS levels significantly decreased from 130 to 124 mg/dl in Group B,â€ but HbA1c% decreased insignificantly from 5.26% to 5.24% in Group B.â€ Lipid profile parameters decreased in both groups except triglyceride level, which show insignificant relation in Group B.â€ OS marker malondialdehyde significantly decreased from 1.967 to 1.592 nm/ml in Group Aâ€ and from 0.613 to 0.472 nm/ml in Group B.â€ Plasma antioxidant glutathione shows a significant increase in both groups from 2.117 to 2.405 Î¼mol/L in Group Aâ€ and from 2.631 to 2.811 Î¼mol/L in Group B.â€ Plasma nitric oxide also shows significant increase in both groups from 1.712 to 1.990 Î¼mol/L and from 2.139 to 2.318 Î¼mol/L, respectively. Conclusion: Therefore, ALA is a potent antioxidant and can be used against oxidative injury associate with T2DM.